Physician support of smoking cessation after diagnosis of lung, bladder, or upper aerodigestive tract cancer - Farley, Amanda; Koshiaris, Constantinos; Oke, Jason; Ryan, Ronan; Szatkowski, Lisa; Stevens, Richard; Aveyard, Paul (Annals of Family Medicine, Inc., 2017)
PURPOSE Smoking cessation after a diagnosis of lung, bladder, and upper aerodigestive tract cancer appears to improve survival, and support to quit would improve cessation. The aims of this study were to assess how often general practitioners provide active smoking cessation support for these patients and whether physician behavior is influenced by incentive payments.